Underground material compound and application thereof in perovskite battery

By using highly polar pyridine compounds as buried base materials in perovskite batteries, the buried base layer is formed to passivate Ni2+ and Pb2+ defects, the problem of low efficiency and stability of perovskite batteries is solved, higher open circuit voltage and hole transmission efficiency are achieved, and the stability of the battery is improved.

CN119569647AActive Publication Date: 2025-03-07XIAMEN ZIJIN NEW ENERGY & NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411749774.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing perovskite batteries have poor efficiency and stability due to poor matching of nickel oxide and perovskite layer energy levels and high interfacial defect density.

Method used

A highly polar pyridine compound is used as the buried base material, and a buried base layer is formed between the hole transport layer and the perovskite layer by spin coating to passivate the Ni2+ in the nickel oxide layer and the Pb2+ defects in the perovskite layer to reduce the interfacial defect density.

Benefits of technology

The open circuit voltage and hole transmission efficiency of perovskite batteries are improved, the stability of the battery is enhanced, non-radiative recombination is reduced, and degradation caused by direct contact between Ni3+ in the nickel oxide layer and I- in the perovskite layer is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569647A_ABST
    Figure CN119569647A_ABST
Patent Text Reader

Abstract

The invention provides a buried material compound and application thereof in a perovskite battery, and relates to the technical field of perovskite batteries. The structure of the buried material compound is # imgabs0 #, at least one of R1 and R2 is an organic group containing one or two or more elements of O, S, N and P, or at least one of R1 and R2 contains halogen. The bottom burying compound is used for a bottom burying layer of the perovskite solar cell, and the stability of the photoelectric conversion efficiency of the perovskite solar cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite cells and relates to a buried material compound and an application thereof in a perovskite cell. Background Art

[0002] Perovskite materials have attracted widespread attention due to their excellent optoelectronic properties. In just over a decade, the efficiency of perovskite cells has increased from 3.8% to 26.1%. In existing technologies, nickel oxide is widely used as the hole transport layer of inverse perovskite solar cells due to its low cost, simple preparation process and good stability.

[0003] Due to the poor matching of nickel oxide and perovskite layer energy levels and high interface defect density, the efficiency and stability of the entire perovskite battery are not high. The main component of the nickel oxide hole transport layer is Ni 3+ , passivation Ni 2+ To improve Ni 3+ The ratio is an effective way to improve the hole transport efficiency. In addition, perovskite itself also has some defects, including iodine defects, lead defects, cation vacancy defects, etc. These defects will greatly reduce the charge transfer efficiency and battery stability. The study found that a buried layer can be set between the nickel oxide hole transport layer and the perovskite layer to passivate the Ni in the nickel oxide layer. 2+ and Pb in the perovskite layer 2+ The defect strategy promotes charge transfer, increases the crystallinity of perovskite and reduces the defect density at the interface, reduces non-radiative recombination, increases the open circuit voltage and hole transfer efficiency of the battery, and also avoids the Ni in the nickel oxide layer. 3+ I in the perovskite layer - Direct contact leads to the degradation of perovskite cells, which improves the efficiency and stability of perovskite cells.

[0004] Currently, the industry has proposed a variety of bottom burial materials, and the applicant believes that the bottom burial materials need to be further improved. Summary of the invention

[0005] The applicant has found that using a highly polar pyridine compound as the bottom material can effectively passivate the Ni in the nickel oxide layer. 2+ And improve Ni 3+ ratio, and passivate the Pb in the perovskite layer 2+ Defects are eliminated and the crystallinity of the perovskite layer is increased, thereby increasing the open circuit voltage and hole transport efficiency of the perovskite cell as a whole. Based on this, the present invention provides a buried material compound and its application in a perovskite cell.

[0006] The technical solution of the present invention is as follows:

[0007] A bottom buried material compound having a structure shown in the following formula (I):

[0008]

[0009] Among them, R 1 and R 2 At least one of them is an organic group containing one or two or more elements of O, S, N and P, or R 1 and R 2 At least one of them contains a halogen.

[0010] Preferably, the organic group is selected from one of carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, amino, hydroxyl, amide, sulfonamide, carboxyl, C1-C4 acyl, C1-C4 alkoxy, sulfonamide, amidine, linamide and thiol.

[0011] More preferably, the R 1 and R 2 They are not C1-C4 alkoxy at the same time.

[0012] Preferably, the bottom buried material compound has a structure as shown in the following formula (II):

[0013]

[0014] Among them, R 1 is selected from the group consisting of carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, amino, hydroxyl, amide, sulfonamide, carboxyl, C1-C4 acyl, C1-C4 alkoxy, sulfonamide, amidino, linamide, C1-C4 alkyl and sulfhydryl; R 2 One selected from C1-C4 alkyl, C1-C4 alkoxy, C1-C4 carboxyl, Cl, Br, nitro, amino, mercapto and C2-C6 ester.

[0015] More preferably, the bottom buried material compound is selected from one or a combination of two or more of sulfamethylpyridine, methylamide pyridine, 5-methyl-2-pyridinesulfonamide, 6-aminopyridine-3-thioamide, 5-methoxypyridine linamide, 2-amidinopicolinic acid, pyridine-2,5-dicarboxylic acid, 5-chloro-2-hydroxypyridine, 5-bromo-2-nitropyridine, 5-methyl-2-methylpyridine, 2-acetyl-6-bromopyridine, 2,5-pyridinedicarboxylic acid methyl ester and 2-mercapto-5-nitropyridine.

[0016] A perovskite cell comprises a hole transport layer, a buried layer and a perovskite layer stacked in sequence;

[0017] The buried layer is composed of the buried material compound described in any one of the above embodiments.

[0018] Preferably, the buried bottom layer has a thickness of 1-20 nm.

[0019] Preferably, the method for preparing the buried bottom layer comprises:

[0020] Dissolving the bottom embedding material compound in an organic solvent to prepare a 0.1-10 mg / ml solution;

[0021] The solution is spin-coated on the surface of the hole transport layer and annealed to obtain the buried layer.

[0022] More preferably, the purity of the bottom burying material compound is not less than 99%.

[0023] Preferably, the thickness of the hole transport layer is 5-30 nm.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention uses a highly polar compound containing pyridine as a buried bottom material, and can use a spin coating method to form a buried bottom layer between the hole transport layer and the perovskite layer, which can effectively increase the hole transport efficiency and reduce the interface defect density, improve the open circuit voltage and hole transport efficiency of the perovskite solar cell, and enhance the stability of the perovskite solar cell.

[0026] (2) The raw materials of the compound of the buried material of the present invention are easily available, have many selectivities, and have good effects, and thus have good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure of the inverted perovskite solar cell of Example 1.

[0028] 1-ITO conductive glass, 2-nickel oxide hole transport layer, 3-buried bottom layer, 4-three-dimensional perovskite layer, 5-C 60 layer, 6-BCP layer, 7-silver negative electrode layer.

[0029] Figure 2 Comparison of the relationship between current density (JSC) and voltage (V) of the inverse perovskite solar cells of Example 1 and Comparative Example 1.

[0030] Figure 3 The stability comparison of the inverse perovskite solar cells of Example 1 and Comparative Example 1 under high temperature and high humidity tests.

[0031] Figure 4 The stability comparison of the inverse perovskite solar cells of Example 2 and Comparative Example 2 under high temperature and high humidity tests.

[0032] Figure 5The stability comparison of the inverse perovskite solar cells of Example 3 and Comparative Example 3 under high temperature and high humidity tests. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0034] In one aspect, the present invention provides a buried material compound having a structure as shown in the following formula (I):

[0035]

[0036] Among them, R 1 and R 2 At least one of them is an organic group containing one or two or more elements of O, S, N and P, or R 1 and R 2 At least one of them contains a halogen.

[0037] Pyridine is a nitrogen-containing six-membered heterocyclic compound with high polarity. Adding a heteroatom-containing substituent to the pyridine molecular structure further increases the polarity of the buried material compound. In the present invention, a compound having a structure shown in formula (I) - a heteroatom-substituted pyridine is used as the buried material. The buried material has a high polarity, and the heteroatom contains a lone pair of electrons, which can generate a strong van der Waals force and resist metal ions (such as Ni 2+ , Pb 2+ ) has good adsorption and affinity effects, and can effectively adsorb and passivate the Ni of the hole transport layer 2+ and / or Pb in the perovskite layer 2+ , increasing the Ni content in the hole transport layer 3+ The ratio of and / or the defect density of the perovskite layer can be reduced, thereby improving the open circuit voltage and hole transport efficiency of the perovskite solar cell, and isolating the perovskite layer and the hole transport layer to enhance the stability of the perovskite solar cell.

[0038] In a preferred embodiment of the present invention, the organic group is selected from one of carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, amino, hydroxyl, amide, sulfonamide, carboxyl, C1-C4 acyl, C1-C4 alkoxy, sulfonamide, amidine, linamide and thiol.

[0039] In a more preferred embodiment of the present invention, R 1 and R 2 Different from C1-C4 alkoxy. Since the polarity of alkoxy is relatively low, when R 1 and R 2 When it is a C1-C4 alkoxy group, the polarity of the buried material compound is not high enough, and the adsorption and affinity effects for metal ions are poor.

[0040] In the present invention, R 1 and R 2 They can be the same or different. 1 and R 2 When the same, R 1 and R 2 are all organic groups containing one or two or more of the above-mentioned elements O, S, N and P, such as amino, hydroxyl, amide, sulfonamide, carboxyl, carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, etc. 1 and R 2 When different, R 1 and R 2 One of them is the above-mentioned organic group containing one or two or more elements among O, S, N and P, and the other can be the above-mentioned organic group containing one or two or more elements among O, S, N and P or a C1-C4 alkoxy group or a C1-C4 alkyl group.

[0041] In a preferred embodiment of the present invention, the bottom buried material compound is a 2,5-substituted pyridine compound having a structure shown in the following formula (II):

[0042]

[0043] Among them, R 1 is selected from the group consisting of carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, amino, hydroxyl, amide, sulfonamide, carboxyl, C1-C4 acyl, C1-C4 alkoxy, sulfonamide, amidino, linamide, C1-C4 alkyl and sulfhydryl; R 2 One selected from C1-C4 alkyl, C1-C4 alkoxy, C1-C4 carboxyl, Cl, Br, nitro, amino, mercapto and C2-C6 ester.

[0044] In a more preferred embodiment of the present invention, the bottom buried material compound is selected from sulfamethylpyridine, methylamide pyridine, 5-methyl-2-pyridine sulfonamide, 6-aminopyridine-3-thioamide, 5-methoxypyridine linamide, 2-amidinopicolinic acid, pyridine-2,5-dicarboxylic acid, 5-chloro-2-hydroxypyridine, 5-bromo-2-nitropyridine, 5-methyl-2-methylpyridine, 2-acetyl-6-bromopyridine, 2,5-pyridinedicarboxylic acid methyl ester and 2-mercapto-5-nitropyridine, or a combination of two or more thereof.

[0045] In another aspect, the present invention provides a perovskite cell, comprising a hole transport layer, a buried layer and a perovskite layer stacked in sequence;

[0046] The buried layer is composed of the buried material compound described in any one of the above embodiments.

[0047] In the present invention, a buried layer composed of the above-mentioned buried material compound is disposed between the hole transport layer and the perovskite layer to isolate the hole transport layer and the perovskite layer. 2+ It has good adsorption and affinity effects and can effectively adsorb and passivate the Pb in the perovskite layer. 2+ , reducing the defect density of the perovskite layer, thereby improving the open circuit voltage of the perovskite solar cell. When the hole transport layer is a nickel oxide layer, the buried layer has a great influence on the Ni 2+ It has good adsorption and affinity effects and can effectively adsorb and passivate the Ni of the hole transport layer 2+ , increasing the Ni content in the hole transport layer 3+ ratio, improving the hole transport efficiency.

[0048] For example, the perovskite cell of the present invention can be a transverse structure, which can include a substrate, a positive electrode layer, a hole transport layer, a buried layer, a perovskite layer, an electron transport layer and a negative electrode layer stacked in sequence from bottom to top. For example, the substrate can be glass, a flexible substrate, a heterojunction cell, a crystalline silicon cell or other thin film solar cells. For example, the thickness of the perovskite layer can be 300-900nm, and the general structural formula of the perovskite can be expressed as Cs a R b FA c MA d PbI x Br y , wherein FA represents formamidine, MA represents methylamine, a≥0, b≥0, c≥0, d≥0, a+b+c+d=1, a+b≤0.2, x+y=3, y≤0.6. For example, the positive electrode layer includes ITO, FTO or IZO. For example, the electron transport layer includes C 60 +BCP, PCBM+BCP or C 60 +SnO 2 For example, the negative electrode layer includes an ITO electrode, a silver electrode, a copper electrode, a gold electrode or an aluminum electrode.

[0049] In a preferred embodiment of the present invention, the thickness of the buried layer is 1-20 nm. For example, the thickness of the buried layer can be any value of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, etc., without any particular limitation.

[0050] In a preferred embodiment of the present invention, the method for preparing the buried bottom layer comprises:

[0051] Dissolving the bottom embedding material compound in an organic solvent to prepare a 0.1-10 mg / ml solution;

[0052] The solution is spin-coated on the surface of the hole transport layer and annealed to obtain a buried bottom layer.

[0053] The buried bottom layer is prepared by spin coating, and the thickness of nanometer level can be obtained, and the film layer is relatively uniform. The above-mentioned organic solvent can be any one of methanol, ethanol, isopropanol, acetonitrile, toluene, dimethyl sulfoxide, DMF, DMAc and acetone, or a mixed solvent of multiple kinds. The spin coating speed can be 3000-5000r / min, the annealing temperature can be 20℃-100℃, and the annealing time can be 1min-10min. There is no special restriction on the concentration of the prepared solution, which can be 0.1mg / ml, 0.5mg / ml, 1mg / ml, 2mg / ml, 3mg / ml, 4mg / ml, 5mg / ml, 6mg / ml, 7mg / ml, 8mg / ml, 9mg / ml, 10mg / ml, etc.

[0054] In a more preferred embodiment of the present invention, the purity of the bottom burying material compound is not less than 99%. If the purity of the bottom burying material compound is insufficient and there are more impurities, the function and effect of the bottom burying material compound will be affected.

[0055] In a preferred embodiment of the present invention, the hole transport layer has a thickness of 5-30 nm. For example, the hole transport layer can be a nickel oxide hole transport layer, and the thickness can be any value of 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, etc., without particular limitation.

[0056] The perovskite solar cell of the present invention has a buried layer composed of the buried material composition between the hole transport layer and the perovskite layer, and has high photoelectric conversion efficiency and open circuit voltage, while having high stability of photoelectric conversion efficiency.

[0057] The technical solution of the present invention is further described and illustrated according to various embodiments below.

[0058] Example 1

[0059] This embodiment provides a buried material compound and a method for preparing an inverse perovskite cell, comprising the following steps (1)-(5):

[0060] (1) Prepare a solution of a bottom burying material compound, wherein the bottom burying material compound is 2-sulfonamide-5-methylpyridine, the solvent is isopropanol, and the concentration of the bottom burying material compound is 0.75 mg / ml.

[0061] (2) Providing ITO conductive glass, spin coating a nickel oxide nano-solution on the surface of the ITO conductive glass to form a hole transport layer, wherein the thickness of the hole transport layer is 10 nm.

[0062] (3) Spin coating the buried bottom material compound solution on the surface of the nickel oxide layer at a rotation speed of 4000 r / min to form a buried bottom liquid film; annealing the buried bottom liquid film at an annealing temperature of 80° C. for 5 min to obtain a buried bottom layer with a thickness of 8 nm.

[0063] (4) A three-dimensional perovskite layer is formed on the surface of the hole transport layer by spin coating. The material of the three-dimensional perovskite layer is Cs 0.05 FA 0.95 PbI 3 , thickness is 600nm.

[0064] (5) Using vacuum evaporation technology, 20 nm thick C is deposited on the surface of the three-dimensional perovskite layer. 60 layer, 8nm thick BCP layer and 120nm silver negative electrode layer, the effective area is 0.09cm 2 The inverted perovskite solar cell has a schematic diagram as shown in the attached figure. Figure 1 shown.

[0065] The photoelectric conversion efficiency of the perovskite solar cell prepared in this embodiment was tested, and the initial efficiency was 23.6%, the open circuit voltage was 1.18V, and the short circuit current density was 23.8mA / cm 2 The fill factor is 84.2%. The efficiency of the prepared perovskite solar cell is 94% of the initial efficiency after running for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%), with high initial efficiency and good efficiency stability.

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 1 is that no buried bottom layer is provided between the three-dimensional perovskite layer and the nickel oxide hole transport layer in Example 1. The remaining steps remain unchanged.

[0068] The photoelectric conversion efficiency of the perovskite solar cell prepared in this comparative example was tested, and the initial efficiency was 21.6%, the open circuit voltage was 1.07V, and the short circuit current density was 24.0mA / cm 2 The fill factor is 83.8%. The prepared perovskite solar cell maintains 55% of the initial efficiency after operating for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%).

[0069] The comparison between the current density (JSC) and voltage (V) of the inverse perovskite solar cell of this comparative example and Example 1 and the stability comparison under high temperature and high humidity test are shown in the attached figure. Figure 2 and attached Figure 3 shown.

[0070] Example 2

[0071] This embodiment provides a buried material compound and a method for preparing an inverse perovskite cell, comprising the following steps (1)-(6):

[0072] (1) Prepare a bottom burying material compound solution, wherein the bottom burying material compound is 5-methyl-2-pyridinesulfonamide, the solvent is a mixed solution of isopropanol and DMF (volume ratio is 19:1), and the concentration of the bottom burying material compound is 0.5 mg / ml.

[0073] (2) providing a heterojunction battery, and forming an ITO positive electrode layer with a sputtering thickness of 30 nm on the surface of the heterojunction battery by a physical vapor deposition process (PVD);

[0074] (3) A 10 nm thick nickel oxide hole transport layer is formed on the surface of the ITO layer of the conductive glass by magnetron sputtering.

[0075] (4) Spin coating the buried bottom material compound solution on the surface of the nickel oxide layer at a rotation speed of 4000 r / min to form a buried bottom liquid film; annealing the passivation liquid film at an annealing temperature of 60° C. for 8 min to obtain a buried bottom layer with a thickness of 5 nm.

[0076] (5) A three-dimensional perovskite layer is formed on the surface of the hole transport layer by spin coating. The material of the three-dimensional perovskite layer is Cs 0.05 FA 0.8 MA 0.15 PbI 2.4 Br 0.6 , thickness is 650nm.

[0077] (6) A 20 nm thick C layer is deposited on the surface of the passivation layer by vacuum evaporation process. 60 Layer, atomic layer deposition 20nm thick SnO 2 The effective area is 1cm 2 Perovskite / heterojunction tandem solar cells.

[0078] The photoelectric conversion efficiency of the prepared perovskite / heterojunction stacked cell was tested, and the initial efficiency was 28.0%. The efficiency of the prepared perovskite / heterojunction stacked cell was 92% of the initial efficiency after running for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%).

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 2 is that no buried bottom layer is provided between the three-dimensional perovskite layer and the nickel oxide hole transport layer in Example 2. The remaining steps remain unchanged.

[0081] The photoelectric conversion efficiency of the perovskite solar cell prepared in this comparative example was tested, and the initial efficiency was 26.7%. The prepared perovskite solar cell maintained 52% of the initial efficiency after operating for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%).

[0082] The stability comparison of the inverse perovskite solar cell of this comparative example and Example 2 under high temperature and high humidity test is shown in the attached figure. Figure 4 shown.

[0083] Example 3

[0084] This embodiment provides a buried material compound and a method for preparing a buried layer of an inverse perovskite cell, comprising the following steps (1)-(6):

[0085] (1) Prepare a solution of a bottom burying material compound, wherein the bottom burying material compound is 6-aminopyridine-3-thioamide, the solvent is methanol, and the concentration of the bottom burying material compound is 1 mg / ml.

[0086] (2) A copper indium gallium selenide thin film solar cell is provided, and a 20 nm ITO positive electrode layer is formed on the electrode surface of the copper indium gallium selenide thin film solar cell by a physical vapor deposition process (PVD).

[0087] (3) A nickel oxide hole transport layer is formed on the surface of the ITO conductive glass by a spin coating method. The thickness of the hole transport layer is 12 nm.

[0088] (4) Spin coating the buried material compound solution on the surface of the nickel oxide hole transport layer to form a buried liquid film at a rotation speed of 4000 r / min; annealing the buried liquid film at an annealing temperature of 70° C. for 6 min to obtain a buried layer with a thickness of 10 nm.

[0089] (5) A three-dimensional perovskite layer is formed on the surface of the hole transport layer by spin coating. The material of the three-dimensional perovskite layer is Cs 0.05 FA 0.77 MA 0.22 PbI 2.35 Br 0.65 , thickness is 700nm.

[0090] (6) A 15 nm thick C layer is deposited on the surface of the passivation layer by vacuum evaporation process. 60 Layer, atomic layer deposition 20nm thick SnO 2 The effective area is 1cm 2 Perovskite / copper indium gallium selenide tandem solar cell.

[0091] The photoelectric conversion efficiency of the perovskite / copper indium gallium selenide tandem cell prepared in this embodiment was tested, and the initial efficiency was 21.7%. The prepared perovskite / copper indium gallium selenide tandem cell maintained 90% of the initial efficiency after operating for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%).

[0092] Comparative Example 3

[0093] The difference between this comparative example and Example 3 is that no buried bottom layer is provided between the three-dimensional perovskite layer and the nickel oxide hole transport layer in Example 3. The remaining steps remain unchanged.

[0094] The photoelectric conversion efficiency of the perovskite solar cell prepared in this comparative example was tested, and the initial efficiency was 20.2%. The prepared perovskite solar cell maintained 50% of the initial efficiency after operating for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%).

[0095] The stability comparison of the inverse perovskite solar cell of this comparative example and Example 3 under high temperature and high humidity test is shown in the attached figure. Figure 5 shown.

[0096] Example 4

[0097] The difference between this embodiment and embodiment 1 is that in embodiment 1, the bottom burying material compound is adjusted from 2-sulfonamide-5-methylpyridine to 5-methyl-2-pyridinecarboxamide, and the other steps remain unchanged.

[0098] The photoelectric conversion efficiency of the perovskite solar cell prepared in this embodiment was tested, and the initial efficiency was 23.1%. The efficiency of the prepared perovskite solar cell was 91% of the initial efficiency after running for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%), with high initial efficiency and good efficiency stability.

[0099] Example 5

[0100] The difference between this embodiment and embodiment 1 is that in embodiment 1, the bottom burying material compound is adjusted from 2-sulfonamide-5-methylpyridine to 5-methoxypyridinamide, the concentration of the bottom burying material compound solution is 2 mg / ml, and the thickness of the burying layer is 15 nm. The other steps remain unchanged.

[0101] The photoelectric conversion efficiency of the perovskite solar cell prepared in this embodiment was tested, and the initial efficiency was 23.3%. The efficiency of the prepared perovskite solar cell was 92% of the initial efficiency after running for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%), with high initial efficiency and good efficiency stability.

[0102] Example 6

[0103] The difference between this embodiment and embodiment 2 is that in embodiment 2, the bottom burying material compound is adjusted from 5-methyl-2-pyridinesulfonamide to 5-bromo-2-nitropyridine, the concentration of the bottom burying material compound solution is 1 mg / ml, and the thickness of the burying layer is 12 nm. The other steps remain unchanged.

[0104] The photoelectric conversion efficiency of the perovskite / heterojunction stacked cell prepared in this embodiment was tested, and the initial efficiency was 27.5%. The efficiency of the prepared perovskite / heterojunction stacked cell was 91% of the initial efficiency after running for 1200 hours under high temperature and high humidity conditions (85°C, RH 85%), with high initial efficiency and good efficiency stability.

[0105] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A bottom buried material compound, characterized in that: It has the structure shown in the following formula (I), Among them, at least one of R1 and R2 is an organic group containing one or two or more elements of O, S, N and P, or at least one of R1 and R2 contains halogen.

2. The bottom embedding material compound according to claim 1, characterized in that: The organic group is selected from one of carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, amino, hydroxyl, amide, sulfonamide, carboxyl, C1-C4 acyl, C1-C4 alkoxy, sulfonamide, amidine, linamide and mercapto.

3. The bottom embedding material compound according to claim 2, characterized in that: The R1 and R2 are not C1-C4 alkoxy groups at the same time.

4. The bottom embedding material compound according to claim 1, characterized in that: The buried material compound has a structure shown in the following formula (II): Wherein, R1 is selected from one of carbonyl, nitro, thiocarbonyl, phosphonyl, sulfonic acid, ester, thioamide, amino, hydroxyl, amide, sulfonamide, carboxyl, C1-C4 acyl, C1-C4 alkoxy, sulfonamide, amidino, linamide, C1-C4 alkyl and sulfhydryl; R2 is selected from one of C1-C4 alkyl, C1-C4 alkoxy, C1-C4 carboxyl, Cl, Br, nitro, amino, sulfhydryl and C2-C6 ester.

5. The bottom embedding material compound according to claim 4, characterized in that: The bottom buried material compound is selected from one or a combination of two or more of sulfamethylpyridine, methylamide pyridine, 5-methyl-2-pyridine sulfonamide, 6-aminopyridine-3-thioamide, 5-methoxypyridine linamide, 2-amidinopyridinecarboxylic acid, pyridine-2,5-dicarboxylic acid, 5-chloro-2-hydroxypyridine, 5-bromo-2-nitropyridine, 5-methyl-2-methylpyridine, 2-acetyl-6-bromopyridine, 2,5-pyridinedicarboxylic acid methyl ester and 2-mercapto-5-nitropyridine.

6. A perovskite battery, characterized in that: It comprises a hole transport layer, a buried layer and a perovskite layer stacked in sequence; The buried layer is composed of the buried material compound according to any one of claims 1-5.

7. The perovskite cell according to claim 6, characterized in that: The thickness of the buried bottom layer is 1-20 nm.

8. The perovskite battery according to claim 6, characterized in that: The method for preparing the buried bottom layer comprises: Dissolving the bottom embedding material compound in an organic solvent to prepare a 0.1-10 mg / ml solution; The solution is spin-coated on the surface of the hole transport layer and annealed to obtain the buried layer.

9. The perovskite cell according to claim 8, characterized in that: The purity of the bottom burying material compound is not less than 99%.

10. The perovskite battery according to claim 6, characterized in that: The thickness of the hole transport layer is 5-30 nm.

Citation Information

Patent Citations

  • Perovskite solar cell and preparation method thereof

    CN116234329A

  • Perovskite solar cell and preparation method thereof

    CN116234395A

  • Buried interface modified perovskite solar cell module and preparation method thereof

    CN118139435A

  • Perovskite solar cell

    CN118266281A

  • Preparation method of perovskite solar cell module based on buried modification of thiophene amine small molecule compound

    CN118510352A